AERODYNAMICS OPTIMIZATION OF THE UNIVERSITI TEKNOLOGI PETRONAS PERODUA ECO CHALLENGE 2011 CAR - ROSLAN, MUHAMMAD SHAFIQ (2011)
THIS IS THE CONSTRUCTION AND REPORT ON THE EXPERIMENTATION OF A SHAPE OPTIMIZATION METHOD APPLIED TO AERODYNAMIC DESIGN OF A CAR. THE SCOPES OF STUDY AREAS ARE IN RESEARCH, DESIGNING AND ANALYSIS IN COMPUTATIONAL FLUID DYNAMICS TOOL. THE RESULTS FROM TEH COMPUTATIONAL FLUID DYNAMICS SOFTWARE WILL BE COMPARE WITH THE RESULT FROM WIND TUNNEL EXPERIMENT.